Assessing detergent‐mediated virus inactivation, protein stability, and impurity clearance in biologics downstream processes. Issue 4 (8th February 2022) - Feroz, Hasin; Chennamsetty, Naresh; Byers, Sara; Holstein, Melissa; Li, Zheng J.; Ghose, Sanchayita
Abstract: Detergent‐mediated virus inactivation (VI) provides a valuable orthogonal strategy for viral clearance in mammalian processes, in particular for next‐generation continuous manufacturing. Furthermore, there exists an industry‐wide need to replace the conventionally employed detergent Triton X‐100 with eco‐friendly alternatives. However, given Triton X‐100 has been the gold standard for VI due its minimal impact on protein stability and high inactivation efficacy, inactivation by other eco‐friendly detergents and its impact on protein stability is not well understood. In this study, the sugar‐based detergent commonly used in membrane protein purification, n ‐dodecyl‐β‐ d ‐maltoside was found to be a promising alternative for VI. We investigated a panel of detergents to compare the relative VI efficacy, impact on therapeutic quality attributes, and clearance of the VI agent and other impurities through subsequent chromatographic steps. Detergent‐mediated inactivation and protein stability showed comparable trends to low pH inactivation. Using experimental and modeling data, we found detergent‐mediated product aggregation and its kinetics to be driven by extrinsic factors such as detergent and protein concentration. Detergent‐mediated aggregation was also impacted by an initial aggregation level as well as intrinsic factors such as the protein sequence and detergent hydrophobicity, and critical micelle concentration. Knowledge gained here on factors driving product stability and VI provides valuable insight to design, standardize, and optimize conditions (concentration and duration of inactivation) for screening of detergent‐mediated VI. Abstract : Feroz et al. discuss an efficient strategy for screening detergent‐mediated virus inactivation (VI) conditions for purification of therapeutics of mammalian origin. The authors demonstrate the first instance of using the eco‐friendly sugar‐based detergent  n ‐dodecyl‐β‐ d ‐maltopyranoside for inactivation of Bio Safety Level‐2 viruses. This study investigates the interplay of the detergent, protein, and virus system in driving protein stability and detergent‐mediated VI.